2023
DOI: 10.1007/s00432-023-04711-4
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of sex-based clinicopathological differences among patients with gastrointestinal neuroendocrine neoplasms in Europe

Abstract: Background Previous studies have found variations in cancer types, tumor progression, and disease outcomes between men and women. However, there is limited knowledge of the effect of sex on gastrointestinal neuroendocrine neoplasms (GI-NENs). Methods We identified 1354 patients with GI-NEN from the IQVIA’s Oncology Dynamics database. Patients were derived from four European countries (Germany, France, the United Kingdom (UK), Spain). Clinical and tumor rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…Evaluating studies of varying intent (not aimed at evaluating gender differences or focused on CaS), women seemed to have improved outcomes, a slight advantage in response to therapy, especially for liver metastases, and better survival compared to men [ 3 , 18 21 , 43 46 ]. However, neither our study nor previous analyses revealed any gender-related differences in treatment modalities, response to therapy, and patient outcomes in NEN patients [ 4 , 42 ]. However, when evaluating the therapeutic outcomes, limitations of our study should be taken in account, mostly due to its retrospective nature, the relatively small sample size when subdividing patients according to therapy, and the partial overlap of patients between the treatment groups which could not allow a clear separation of therapeutic effects.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Evaluating studies of varying intent (not aimed at evaluating gender differences or focused on CaS), women seemed to have improved outcomes, a slight advantage in response to therapy, especially for liver metastases, and better survival compared to men [ 3 , 18 21 , 43 46 ]. However, neither our study nor previous analyses revealed any gender-related differences in treatment modalities, response to therapy, and patient outcomes in NEN patients [ 4 , 42 ]. However, when evaluating the therapeutic outcomes, limitations of our study should be taken in account, mostly due to its retrospective nature, the relatively small sample size when subdividing patients according to therapy, and the partial overlap of patients between the treatment groups which could not allow a clear separation of therapeutic effects.…”
Section: Discussioncontrasting
confidence: 97%
“…Our analysis did not reveal any significant differences in pathological grade, tumor stage, and distant metastases at diagnosis of CaS between men and women. Scarce data exist in the literature providing evidence that female patients are diagnosed with G1 and low G2 NEN more frequently that male patients [ 2 , 3 , 42 ], but data specifically focused on CaS are not available. In our study, the majority of patients were diagnosed with G1–G2 grading, and no statistically significant difference was found related to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Leoncini et al [ 17 ] systematically analyzed 11 studies involving 72,048 patients and reported that males exhibit a greater incidence of high-grade NENs. This finding was supported by other studies, which also demonstrated that males are more likely to develop malignant NENs [ 1 , 18 , 19 ]. Differences in dietary habits may contribute to differences in the incidence of GEP-NENs between males and females [ 20 , 21 ].…”
Section: Epidemiologysupporting
confidence: 87%
“…This allows for the detection of tumors by molecular imaging of SSTRs via radionuclide-labeled somatostatin analogs (SSAs), single-photon emission computed tomography (SPECT), or positron emission tomography (PET). The commonly used radionuclides in SPECT imaging are 99m Tc, 131 I, and 111 In, and the positron nuclides used in PET are 18 F and 68 Ga. To date, 68 Ga-DOTA-DSA PET/ CTs, such as 68 Ga-DOTATATE, 68 Ga-DOTANOC, and 68 Ga-DOTATOC PET/CTs, have been developed to diagnose GEP-NENs [85]. Several studies have proven that 68 Ga-DOTATATE PET/CT has high accuracy and has become the preferred strategy for diagnosing GEP-NENs [81,[86][87][88][89].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation